2016
DOI: 10.1103/physrevb.94.165434
|View full text |Cite
|
Sign up to set email alerts
|

Nano-cross-junction effect on phonon transport in silicon nanowire cages

Abstract: Wave effects of phonons can give rise to controllability of heat conduction beyond that by particle scattering at surfaces and interfaces. In this work, we propose a new class of 3D nanostructure: a silicon-nanowire-cage (SiNWC) structure consisting of silicon nanowires (SiNWs) connected by nano-cross-junctions (NCJs). We perform equilibrium molecular dynamics (MD) simulations, and find an ultralow value of thermal conductivity of SiNWC, 0.173 Wm -1 K -1 , which is one order lower than that of SiNWs.By further… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 120 publications
(118 citation statements)
references
References 37 publications
5
112
1
Order By: Relevance
“…Data procurement is to acquire physical properties and structural information of given materials. Both calculations (such as first-principles, [20,23] molecular dynamics [22,24,25] and lattice dynamics [26,27] etc. ), experiments [28] and online libraries [29], have been used to collect these data.…”
Section: Data Procurementmentioning
confidence: 99%
“…Data procurement is to acquire physical properties and structural information of given materials. Both calculations (such as first-principles, [20,23] molecular dynamics [22,24,25] and lattice dynamics [26,27] etc. ), experiments [28] and online libraries [29], have been used to collect these data.…”
Section: Data Procurementmentioning
confidence: 99%
“…Ma et al investigated local resonant effects in 3D silicon nanowire cages, and Zhu et al considered bulk silicon with internal amorphous regions acting as an environment of nanoresonators (see ref. for a survey of potential configurations using atomically disordered inclusions).…”
Section: Thermal Transport In Nanostructured Membranesmentioning
confidence: 99%
“…It was shown that these nanoparticles can act as resonators that impedes phonon transport [192]. Note that the phonon resonance effect and its influence on thermal conductivity has also been investigated in substructures such as thin films with surface pillars [193][194][195][196][197][198]. Figure 8 shows that a schematic of wave packet simulation in silicon matrix with embedded germanium nanoparticles, and the PTP through the system.…”
Section: Resonance Effect By Embedded Nanoparticlesmentioning
confidence: 99%